Surface stresses associated with arrested dykes in rift zones - Gudmundsson, Agust (Bulletin of volcanology, 2003)
Many theoretical models predict that arrested dykes may generate major grabens at rift-zone surfaces. Arrested dyke tips in eroded rift zones, however, are normally not associated with major grabens or normal faults that could be generated by dyke-induced stresses ahead of the tips, and normal faults and grabens tend to be less common in those parts of eroded rift zones where dykes are comparatively abundant. Similarly, there are feeder dykes, as well as dykes arrested a few metres below the surface, that do not generate faults or grabens at the surface. Here I propose that this discrepancy between theoretical models and field observations may be explained by the mechanical layering of the crust. Numerical models presented here show that abrupt changes in Young's moduli, layers with high dyke-normal compressive stresses (stress barriers), and weak, horizontal contacts have large effects on the dyke-induced stress fields. For the models considered, the surface tensile stresses induced by arrested dykes are normally too small to lead to significant fault or graben formation at the rift-zone surface. The only significant dyke-induced surface tensile stresses (2 MPa) in these models are for a dyke tip arrested at 1 km depth below the surface of a rift zone with a weak contact at 400 m depth and subject to extension. That tensile stress, however, peaks above the ends of the weak horizontal contact, which, in the model considered, occur at distances of 4 km to either side of the dyke, and shows no simple relation to the depth to the dyke tip. Thus, for a layered crust with weak contacts, straightforward inversion of surface geodetic data to infer dyke geometries may result in unreliable results.[PUBLICATION ABSTRACT]